Power and its Logic Mastering Politics - Meier, Dominik (Edition Politik, 2019)
Power is the essence of politics. Whoever seeks to understand and master it must understand its logic. Drawing on two decades of international experience in political consulting, Dominik Meier and Christian Blum give profound and honest insights into the inner workings of power. Introducing their Power Leadership Approach, the authors provide a conceptual analysis of power and present the tools to successfully exercise it in the political domain. "Power and its Logic" is a guidebook for politicians, business leaders, civil society pioneers, public affairs consultants and for every citizen who wants to understand the unwritten rules of politics.